Bamboo shoot insoluble dietary fiber, pea protein and alginate ternary composite hydrogel as well as preparation method and application thereof
By introducing bamboo shoot insoluble dietary fiber into the alginate and pea protein composite gel to adjust the pH value, the problem of insufficient mechanical properties and thermal stability of food gels is solved, and higher mechanical strength and thermal stability are achieved, improving The functional performance of the gel.
Patent Information
- Application Number
- CN202411637646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
Existing food gels have shortcomings in mechanical properties, thermal stability and resource utilization, especially the alginate and pea protein composite gels are fragile, lack elasticity and weak adsorption capacity, and the crosslinking agent is costly and has low efficiency. , The application potential of bamboo shoot insoluble dietary fiber has not been fully explored.
By adjusting the pH value of the reaction system and introducing bamboo shoot insoluble dietary fiber, bamboo shoot insoluble dietary fiber, pea protein, and alginate ternary hydrogel is prepared to reduce the use of chemical crosslinking agents and improve the mechanical strength and heat of the gel. Stability and functional stability.
A denser and uniform gel structure is achieved, mechanical strength and thermal stability are improved, moisture retention ability of the gel network is enhanced, and functional performance of the gel is improved.
Smart Images

Figure CN119279202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food gels, in particular to a ternary composite hydrogel of bamboo shoot insoluble dietary fiber, pea protein and alginate, and a preparation method and application thereof. Background Art
[0002] Hydrogel is a polymer material with a three-dimensional network structure, which shows good biocompatibility, high water retention, adsorption performance and sustained release function within a certain range. This makes it suitable for a variety of fields, including food processing, bioengineering, modern agriculture and other fields. Adding different matrices (the main component of making gels) can produce gels with different functional properties. Recent research on food gels has mainly focused on the detection and development of protein-polysaccharide combinations.
[0003] Pea protein isolate (PPI) and sodium alginate (SA) are widely used in food gels. PPI is rich in essential amino acids, has nutritional value, is hypoallergenic and non-GMO. However, PPI has relatively low solubility and disulfide bond content, and the gel formed is not good. SA is a binary linear polysaccharide extracted from marine brown algae with good pH responsiveness and gel properties, and can form gels under low pH conditions. Nevertheless, SA gels have some disadvantages, including fragility, lack of elasticity, weak adsorption capacity and poor mechanical properties. Combining PPI with SA is usually an effective way to address the shortcomings of single-component gels, which can introduce a series of structural features and physicochemical properties to the gel system. However, most of these composite gels are prepared by ionic or chemical cross-linking methods, such as using calcium chloride / calcium carbonate or EDC / NHS / gluconolactone (GDL). These cross-linkers not only cause unwanted reactions between materials during the cross-linking process, but also leave residues, are expensive and take a long time to cross-link. In order to reduce the use of cross-linking agents and further improve the gel properties of the SA-PPI binary system, adjusting the pH of the reaction system (pH-driven method) and introducing specific materials such as insoluble dietary fiber into the binary gel are better options.
[0004] Bamboo shoots, as a typical agricultural product, produce a large amount of byproducts rich in insoluble dietary fiber (IDF) during processing. These byproducts are often not fully utilized or improperly handled, resulting in resource waste and environmental pollution. Previous studies have shown that IDF can enhance hydrophilicity, form a porous structure, and form a large number of interconnected hydrogel networks, thereby improving the mechanical toughness of hydrogels. However, current research and practical applications of IDF have not yet fully explored its huge potential.
[0005] Therefore, expanding the application of IDF in bamboo shoot byproducts has become a focus of modern research. However, insufficient research on the gel properties and structural characteristics of ternary composite gels has hindered the development of gel foods. Summary of the invention
[0006] In order to solve the above technical problems existing in the prior art, the present invention provides a ternary composite hydrogel of bamboo shoot insoluble dietary fiber, pea protein and alginate and a preparation method and application thereof. Specifically, the present invention is achieved through the following technical solutions:
[0007] A method for preparing a ternary composite hydrogel of bamboo shoot insoluble dietary fiber, pea protein and alginate comprises the following steps:
[0008] (1) preparing a sodium alginate (SA) solution with a concentration of 2.5% (w / v) and a pea protein isolate (PPI) solution with a concentration of 3.0% (w / v);
[0009] (2) stirring the two solutions and then mixing them in a ratio of 3:4 (v / v) to form a SA-PPI composite solution;
[0010] (3) adding insoluble dietary fiber (IDF) to the SA-PPI solution to a final IDF concentration of 1.0%-3.0%, and stirring the solution sufficiently to obtain a PPI-SA-IDF complex;
[0011] (4) Transfer the PPI-SA-IDF complex mixed solution into a bottle;
[0012] (5) Then, the pH value of the mixed solution was adjusted to <3 using hydrochloric acid and sodium hydroxide respectively.
[0013] Furthermore, the sodium alginate (SA) solution and the pea protein isolate (PPI) solution are prepared in sterile distilled water.
[0014] Furthermore, the stirring in step (2) is carried out at 25° C. for 3 hours.
[0015] Furthermore, the culturing in step (2) is carried out at a temperature of 28-32°C for 48-96 hours.
[0016] Furthermore, in step (3), insoluble dietary fiber (IDF) is added to the SA-PPI solution so that the final IDF concentration reaches 1.0%-3.0%.
[0017] Furthermore, the step (5) is carried out at room temperature.
[0018] Furthermore, the concentration of the hydrochloric acid in step (5) is 1M.
[0019] Furthermore, in step (5), the pH value of the mixed solution is adjusted to 1.0-2.0.
[0020] The bamboo shoot insoluble dietary fiber, pea protein and alginate ternary composite hydrogel prepared by the above method can be used for embedding active substances, or used in agriculture, environmental protection and other aspects.
[0021] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0022] (1) Most of these composite gels are prepared by ionic or chemical crosslinking methods, such as using calcium chloride / calcium carbonate or EDC / NHS / gluconolactone). These crosslinking agents not only cause unnecessary reactions between materials during the crosslinking process, but also leave residues, are expensive, and take a long time to crosslink. In order to reduce the use of crosslinking agents and further improve the gel properties of the SA-PPI binary system, the present invention reduces the use of chemical crosslinking agents and improves the properties of the hydrogel by adjusting the pH of the reaction system (pH-driven method) and introducing insoluble dietary fiber into the binary gel.
[0023] (2) The hydrogel finally obtained in the present application has the following advantages: the structure becomes more dense and uniform, and the deformation ability is also reduced; the mechanical strength is good, and it provides the possibility for the encapsulation of bioactive molecules; it shows higher thermal stability; the crystallinity is higher, and the mechanical strength and functional stability are improved; it can enhance the ability of the gel network to retain water within its structure, and its porous structure helps to stabilize water molecules. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the appearance of the composite hydrogel.
[0025] Figure 2 It is the infrared spectrum of the composite hydrogel.
[0026] Figure 3 is the thermal stability of the composite hydrogel.
[0027] Figure 4 It is the XRD pattern of the composite hydrogel.
[0028] Figure 5 This is an MRI image of the composite hydrogel.
[0029] Figure 6 is the SEM image of the composite hydrogel.
[0030] Figure 7 It is a flow chart of the preparation of the composite hydrogel of the present application. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0032] Extraction of IDF from Bamboo Shoot Byproducts
[0033] The bamboo shoot byproducts were first cleaned with water, trimmed to a suitable size, and then dried in an oven at 45°C for 48 hours. After drying, they were crushed and passed through a 100-mesh sieve. The powder solution of the bamboo shoot byproducts was adjusted to 11 with distilled water and 0.5M NaOH. After mixing, they were heated in an 80°C water bath for 2 hours and then centrifuged at 8000 rpm for 15 minutes. The resulting precipitate was collected, thoroughly washed, and freeze-dried to obtain IDF.
[0034] Preparation of composite hydrogel
[0035] SA (2.5% w / v) and PPI (3.0% w / v) solutions were prepared in sterile distilled water, respectively. The two solutions were stirred at 25°C for 3 hours and then mixed in a ratio of 3:4 (v / v) to form a SA-PPI composite solution. IDF was added to the SA-PPI solution to a final concentration of 1.0%, 2.0% and 3.0%, respectively, and the PPI-SA-IDF complex was obtained by sufficient stirring. Subsequently, the mixed solutions of different mass ratios were transferred to glass vials with a diameter of 20 mm and a height of 25 mm. The pH of the mixed solution was then adjusted to 1.0 and 2.0, respectively, at room temperature using 1M HCl or NaOH. (Gel formation is possible only when pH < 3). This adjustment is to promote gel formation. The resulting composite gel was stored at 4°C for 12 hours before subsequent experiments were started.
[0036] Fourier transform infrared spectroscopy (FTIR) of gel
[0037] 1 mg of the dried sample was mixed with 100 mg of KBr powder to prepare the sample, which was subsequently analyzed using an infrared spectrometer. The resolution of the measurement was 4 cm -1 , scanning range is 4000 to 500 cm -1 .
[0038] Gel Thermal Stability Analysis (TGA)
[0039] At room temperature, 8-10 mg of sample was accurately weighed and placed in a thermogravimetric analyzer. The nitrogen flow rate was set to 40 ml / min, the heating rate was set to 20 °C / min, and the heating range was 30-600 °C. Subsequently, the sample was analyzed in the thermogravimetric analyzer.
[0040] X-ray diffraction analysis (XRD)
[0041] X-ray diffraction analysis was used to evaluate the effects of pH level and IDF incorporation on the diffraction pattern and crystallinity of the hydrogels. The specific operating conditions were: using a Cu target with a diffractometer, a scanning speed of 2° / min, and a scanning range of 2θ=10-80°.
[0042] MRI detection of composite gel
[0043] The proton density of the gel was imaged using a multi-spin echo (MSE) imaging sequence on a magnetic resonance imager. The repetition time was 1500ms, the echo time was 0.2ms, and the center frequency was 21MHz. The gel was imaged in three layers, each with a thickness of 2.0mm, and a color surface map was used to represent the water distribution in the gel.
[0044] Scanning electron microscopy (SEM)
[0045] The microstructure of the gels was measured using a scanning electron microscope. The samples were frozen in liquid nitrogen and subsequently freeze-dried. To prepare the freeze-dried gels for analysis, they were cut into cross sections, glued to aluminum stakes, and coated with a layer of gold. Finally, the samples were imaged using a scanning electron microscope at an accelerating voltage of 20 kV and a magnification of 100 times.
[0046] The results show that the visual appeal and color composition of food have a profound impact on consumer acceptance. Figure 1 As shown, the gels without added insoluble dietary fiber (IDF) (0%) had higher gloss, rounded morphology, and showed higher deformability. After adding IDF, the gloss decreased, but the gel structure became more dense and uniform, and the deformability also decreased. Regardless of the pH value and the presence of IDF, these gels showed a light yellow color.
[0047] Figure 2 It was shown that all characteristic peaks from the spectra of insoluble dietary fiber (IDF), sodium alginate (SA) and pea protein isolate (PPI) were present in the composite sample with only a slight shift. In addition, new absorption peaks appeared in the composite gel, which confirmed that the composite was successfully prepared. Intermolecular interactions, mainly hydrogen bonds and electrostatic forces, help to form a more regular and stronger network structure in the IDF-SA-PPI composite gel. This structure can improve the mechanical strength and provide the possibility for the encapsulation of bioactive molecules.
[0048] The thermal decomposition process of the composite hydrogel between 30℃ and 600℃ can be divided into three stages. The first stage is at about 100℃, which is mainly due to the water absorption and evaporation of the surface. Figure 3 As shown in (C and C1), the main weight loss of the hydrogel at pH 1 occurred in the second stage at about 320 °C, which was mainly due to the depolymerization and decomposition of polysaccharide units, the decarboxylation and dehydration of polysaccharide rings, the degradation of pea protein isolate (PPI), and the weakening of electrostatic interactions. Figure 3In B, the hydrogel with pH 2 and no insoluble dietary fiber (IDF) added showed obvious weight loss at 112°C, while when 3% IDF was added, the main weight loss shifted to 367°C. The IDF-SA-PPI ternary composite hydrogel showed higher thermal stability than the SA-PPI binary hydrogel. The thermal stability of the two groups of composite gels at different pH levels was mainly affected by IDF. This can be attributed to the ability of IDF to bind water within the gel and transfer it to the fiber. In addition, the interaction between IDF and SA-PPI formed a new network structure, which enhanced the stability of the gel. In other words, the denaturation of the IDF-SA-PPI ternary gel requires the absorption of more heat, thereby improving its thermal stability. These results indicate that the ternary composite hydrogel has better thermal stability than the binary SA-PPI hydrogel.
[0049] The term “crystallinity” is used to indicate the proportion of crystalline regions in a hydrogel. The crystallinity of sodium alginate (SA), pea protein isolate (PPI) and insoluble dietary fiber (IDF) is shown in Table 1. Figure 4 As shown in A. IDF, which is composed of cellulose, hemicellulose, lignin, etc., has an amorphous structure. There is an obvious diffraction peak near 22°, indicating that the IDF extracted from bamboo shoot by-products has a typical cellulose type I structure. The more prominent the peak, the higher the content of cellulose and hemicellulose in IDF. Due to the amorphous nature of natural proteins, a specific peak of PPI can be observed at about 20°. SA shows characteristic broad peaks at diffraction angles of 23.9° and 13.1°, which is consistent with previously reported data.
[0050] Unlike SA, PPI, and IDF monomers, the polymers in the composite hydrogel rearranged into an ordered three-dimensional structure during pH adjustment. The most obvious diffraction peaks appeared at 32.9° and 46.4°, which may be due to the acidic conditions that changed the conformation of SA and PPI. This change led to the nonspecific binding of the groups within their molecular structure, forming a crystallization peak of sodium chloride crystals in the SA-PPI gel. A similar phenomenon was also observed in the pea protein-pectin nanocomposite.
[0051] However, the intensity of these two diffraction peaks in the composite hydrogel changed significantly with the mass ratio of IDF. Without IDF, the gel strength was weak and the peak intensity was low. In contrast, the addition of IDF enhanced the gel strength and significantly increased the diffraction peak intensity at 32.9° and 46.4°. This may be due to the hydrogen bonding between the carboxyl groups of the IDF backbone, the carboxyl groups of PPI and SA, and the hydroxyl groups, which enhanced the intensity of the sodium chloride crystallization peak. In addition, the electrostatic interactions between these groups in the composite hydrogel may further promote this effect. The intermolecular hydrogen bonds and electrostatic interactions within the composite hydrogel enhance the orderliness of its structure, increase the crystallinity, and improve the mechanical strength and functional stability.
[0052] Magnetic resonance imaging (MRI) is a non-destructive testing method that can be used to understand the water distribution within the gel. Figure 5 Proton density images of composite gels at different pH values (1 and 2) and different insoluble dietary fiber (IDF) concentrations (0-3% w / v) are shown. The color gradient from red to blue against a blue background (representing anhydrous state) intuitively presents the gradual decrease in proton density, indicating a corresponding decrease in the water content within the gel matrix
[0053] The water distribution varies between samples. The pseudo-color image of the gel without IDF is yellow-green, and the red spots visible on its surface indicate a significantly higher concentration of water molecules within the gel. As the IDF ratio increases, the red spots in the pseudo-color image decrease, indicating a lower free water content and more uniform water distribution within the gel. This means that a higher IDF concentration enhances the ability of the gel network to retain water within its structure. These results are consistent with the observed T2 values, reflecting the transition from free water to fixed water.
[0054] The microstructure of the gel cut surface observed by scanning electron microscopy (SEM) reflects the internal network structure of the gel. Figure 5 As shown, scanning electron microscopy showed that the gel samples exhibited a honeycomb network structure, and there were some differences between the samples.
[0055] At a constant pH value, the gel without the addition of insoluble dietary fiber (IDF) exhibited an uneven pore structure and a fragile, slender network, which may be due to the low structural strength of the sodium alginate (SA) gel. In contrast, the composite gel with the addition of IDF had thicker walls and more uniform pore sizes. When 2% IDF was added, the gel exhibited a uniform honeycomb pore structure, and the largest pore size was observed when 3% IDF was added. An appropriate amount of IDF helps to form a tighter gel network, while an excessive amount of IDF destroys the network, which may be because the porous structure of IDF helps to stabilize water molecules.
[0056] When the amount of IDF added is constant, the pore size distribution of the gel at pH 1 is more uniform than that at pH 2. This may be due to the aggregation of molecular chains at low pH values, at which time the interactions between polymers and within polymers promote the close stacking of the hydrogel network, thus forming a dense three-dimensional structure.
[0057] Overall, the composite hydrogels prepared at pH 1 with 2% IDF addition exhibited a more uniform, dense, and strong three-dimensional network structure, which enhanced their mechanical properties.
[0058] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a ternary composite hydrogel of bamboo shoot insoluble dietary fiber, pea protein and alginate, characterized in that: The steps include: (1) preparing a sodium alginate (SA) solution with a concentration of 2.5% (w / v) and a pea protein isolate (PPI) solution with a concentration of 3.0% (w / v); (2) stirring the two solutions and then mixing them in a ratio of 3:4 (v / v) to form a SA-PPI composite solution; (3) adding insoluble dietary fiber (IDF) to the SA-PPI solution to a final IDF concentration of 1.0%-3.0%, and stirring sufficiently to obtain a PPI-SA-IDF complex; (4) Transfer the PPI-SA-IDF complex mixed solution into a bottle; (5) Then, the pH value of the mixed solution was adjusted to <3 using hydrochloric acid and sodium hydroxide respectively.
2. The preparation method according to claim 1, characterized in that: The sodium alginate (SA) solution and the pea protein isolate (PPI) solution are prepared in sterile distilled water.
3. The preparation method according to claim 1, characterized in that: The stirring in step (2) is performed at 25° C. for 3 hours.
4. The preparation method according to claim 1, characterized in that: The culturing in step (2) is carried out at a temperature of 28-32° C. for 48-96 hours.
5. The preparation method according to claim 1, characterized in that: In the step (3), insoluble dietary fiber (IDF) is added to the SA-PPI solution so that the final IDF concentration reaches 1.0%-3.0%.
6. The preparation method according to claim 1, characterized in that: The step (5) is carried out at room temperature.
7. The preparation method according to claim 1, characterized in that: The concentration of the hydrochloric acid in step (5) is 1M.
8. The preparation method according to claim 1, characterized in that: In the step (5), the pH value of the mixed solution is adjusted to 1.0-2.
0.
9. A bamboo shoot insoluble dietary fiber, pea protein, alginate ternary composite hydrogel, characterized in that: It is prepared by the method according to claim 1.
10. Use of the bamboo shoot insoluble dietary fiber, pea protein and alginate ternary composite hydrogel according to claim 9 in encapsulating active substances.